The Electronic Government - Younus, Khalid Muayad (Journal of Economic, Administrative and Legal Sciences, 2020)
Consider the size of the government sector constitutes a large proportion of the total economic sectors in most countries of the world، as long as dealing with the sector is not confined to a category only، but prevails to all citizens، residents، institutions and others، as long as this deal is multiple in quality and methods and how to model different electronic procedures as an optimal way for the government to enable them to take care of the interests of the public، individuals and institutions electronically using advanced technology without the need for service applicants to move between government departments.Because the government sector as a signification proportion of the total economic sectors in most countries of the world، and because the public sector is not limited to a specific category without the other but prevail all citizens and residents، institution and other، and from here emerged the role of electronic government as an ideal way for the government to enable them to take care of the interests of the public individuals and institution electronically without the need for the applicant of governance، is good governance of the state to take an active conduct at the state level as a whole.
Keywords: e-government; internet; governance; technology